Paleodepositional environment and source rock potential of Paleogene lignite and shale horizons in the Saurashtra Basin, Western India - Alok Kumar; Khairul Azlan Mustapha; Vikram Partap Singh; Bodhisatwa Hazra; P. Gopinathan; Runcie P. Mathews (International Journal of Coal Science & Technology)
Abstract Coal is formed from ancient plants through biochemical and physicochemical stages. Lignite gives a low amount of energy compared to higher rank coal. The Eocene Khadsaliya Formation lignite (Surkha mine) and shale (Khadsaliya mine) sediments were collected to investigate their evolution, maturity, and source rock potential. The main objectives of this study were to update and verify previous claim of possible hydrocarbon showings and to gain new insights about the petroleum potential and paleodepositional conditions using different geochemical analysis approach. The primary methodology employed in this study is the pyrolysis technique and complemented by petrographic analysis. Petrographic indices indicate that Khadsaliya shale and Surkha lignite were deposited in limnic and limno-telmatic conditions, respectively, with slow subsidence rates under mesotrophic hydrological condition. Significant concentration of corpogelinite indicates highly varying water table and low oxygen levels during peat accumulation. At the same time, the presence of funginite, framboidal pyrite, and relatively high sulfur in some studied samples shows marine water influence in the basin. The reflectance values (0.37%–0.57%) reveal that organic matter (OM) in Surkha lignites is immature, while immature to marginally mature in Khadsaliya shale. Furthermore, the pyrolysis data like T max (385°C–430 °C) and production index (PI 0.02–0.13) also indicate immature to marginally mature OM. Oxygen index (OI) versus hydrogen index (HI), T max versus HI, and Total organic carbon (TOC) versus S2 plots of lignite and shale of Khadsaliya Formation indicate that the OM is mainly type III kerogen and can act as fair to good source rock. The distribution of n-alkene/n-alkane doublets, o-Xylene, and 2,3-dimethylthiophene in the Py–GC pyrogram exhibits that most studied shale and lignite samples have type III kerogen and the capability to produce mainly gas.